Thorium dioxide as a nuclear fuel: a scientometric analysis. (1st January 2013) - Kademani, B.S.; Surwase, Ganesh; Sagar, Anil; Bhanumurthy, K.
The present study is aimed at analysing the growth of publications on thorium dioxide (ThO2 ). INIS database is used as a source to analyse the focused areas of this field for the period 1970–2011. The database contained 2337 publications on thorium dioxide. The study analysed the broad features of literature on thorium dioxide, focusing on year-wise publications, highly productive countries, country-wise activity index, domain-wise distribution of publications, highly productive institutes, international collaboration, and most preferred journals for publication in the field.